Developing core national indicators of public attitudes towards the police in Canada - Jackson, Jonathan (Policing and society, 2023)
Police departments regularly conduct public opinion surveys to measure attitudes towards the police. The results of these surveys can be used to shape and evaluate policing policy and practice. Yet the extant evidence base is hampered when people use different methods and when there is no common data standard. In this paper we present a set of 13 core national indicators that can be used by police services across Canada to ensure measurement quality and draw proper comparisons between regions and over time. Having identified a set of 50 survey questions through an expert consultation process, we field those items on a quota sample of 2527 Canadians. Our analysis of the survey data has three stages. First, we use confirmatory factor analysis to assess scale properties. Second, we use substitution analysis to identify 13 single indicators that ‘best stand in’ for each scale. Third, we use the set of 50 and the sub-set of 13 measures to test procedural justice theory for the first time in the Canadian context. Overall, those commissioning and managing public attitudes surveys can use the 13 core indicators as a conceptually-rich and empirically-validated tool through which to understand local survey data in the context of other municipal, provincial, territorial and national contexts.